Vulvovaginal Candidiasis and its Related Factors in Diabetic Women - Ozra Tabatabaei Malazy; Mamak Shariat; Ramin Heshmat; Fereshteh Majlesi; Masoumeh Alimohammadian; Nasibeh Khaleghnejad Tabari; Bagher Larijani (Elsevier, 2007)
Objective: One of the problems of women with diabetes is resistant vulvovaginitis, which is related to some factors such as hyperglycemia, allergy and atopy. One of the most common pathogens associated with this condition is Candida albicans. Thus, most physicians begin antifungal therapy at the patient's first visit, even without para-clinical findings. We aimed to determine the prevalence of Candida vulvovaginitis and factors that cause diabetic women to be prone to this infection. Materials and Methods: This descriptive, analytic cross-sectional study was performed in 160 nonpregnant diabetic women who visited the diabetes clinic of Shariati Hospital in Tehran, Iran from 2002 to 2005. The fasting blood sugar, 2-hour postprandial blood sugar, and glycosylated hemoglobin were measured, and a culture of the vaginal discharge was obtained. Statistical analysis was performed using Fisher's exact test. Results: Seventy-one percent of the women had clinical vaginitis (fungal or bacterial), and 12.5% (20/160) had Candida vaginitis. Microscopic findings for Candida were positive in 12 patients, of whom two had Candida vaginitis. The prevalence of Candida vaginitis together with positive culture was 2.6% (4/160). After including the 10 patients with positive Candida culture together with other clinical vaginitis, the overall prevalence of Candida vaginitis based on positive culture was 8.8% (14/160). There was a significant statistical difference between either mean fasting blood sugar or educational level and infectious vaginal culture. There were no significant associations between positive culture and age, glycosylated hemoglobin, history of allergy, genital hygiene, occupation, kind of treatment, and type or duration of diabetes. Conclusion: We suggest that in the case of clinical vaginitis, especially Candida vulvovaginitis, culture of vaginal discharge should be warranted even if there is a positive smear.